Peran Wadi’ah dan Mudharabah Dalam Profitabilitas Bak Muamalat - Bakti Toni Endaryono; Abdul Robi Jaelani; Agung Prasetyo (Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
The bank's ability to increase profitability is inseparable from its ability to collect funds from the public in various schemes. This study aims to analyze the role of wadiah and mudarobah savings in the profitability of Bank Muamalat. The research method used is quantitative analysis with secondary data from the quarterly financial statements of PT Bank Muamalat Indonesia 2016-2019. The results showed that simultaneously wadi'ah and mudharabah savings had a significant effect on BMI's profitability. While partially, wadiah and mudharabah savings have no significant effect on BMI's profitability.